2022
DOI: 10.3389/fpsyg.2022.966160
|View full text |Cite
|
Sign up to set email alerts
|

Mixed competition and technology licensing in a supply chain

Abstract: Technology licensing as a vital part of business behavior in many industries has drawn a fair amount of attention in industrial organization literature. Most existing literature on licensing decisions assumes that all firms engage in Cournot or Bertrand competition, while the type of mixed competition may affect the choice of the licensor. In this context, what decision will the licensor make faced with different mixed competitions? This paper studies the optimal technology licensing contract of a licensor fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…It is crucial to ensure that academic careers are accessible to everyone, not only for ethical reasons but also because studies from the corporate sector have shown that diversity is beneficial in terms of productivity, outputs, and financial gains. Representation also plays a critical role in shaping our aspirations and achievements [16, 17].…”
Section: Figurementioning
confidence: 99%
“…It is crucial to ensure that academic careers are accessible to everyone, not only for ethical reasons but also because studies from the corporate sector have shown that diversity is beneficial in terms of productivity, outputs, and financial gains. Representation also plays a critical role in shaping our aspirations and achievements [16, 17].…”
Section: Figurementioning
confidence: 99%